ANALISIS MUSIK IRINGAN TARI GAMELAN PADA RITUAL ADAT BAJADI DI DESA MENYUMBUNG KECAMATAN HULU SUNGAI KABUPATEN KETAPANG - Erwin Erwin; Nurmila Sari Djau; Chiristianly Yeri Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research is motivated by a concern for local culture, especially music accompaniment to Gamelan dance. The purpose of this study is to describe the analysis of musical accompaniment to the Gamelan dance in Ketapang Regency. The theory used is about the structure of music, elements of music, musicology, rhythmic patterns, musical forms and chords. The method used in this research is descriptive analytic method with a form of qualitative research. The approach used in this research is the musicology approach. Data obtained from interviews and observations about the musical accompaniment of Gamelan dance in Ketapang Regency, direct communication. Data collection tools used in this study are researchers as the main instrument, cloud guidelines and observation guidelines. Checking the validity of the data of this study uses the extension of observation and triangulation techniques. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Gamelan dance accompaniment is a musical composition with one part and has two sentences. The tempo used is the moderato tempo. This Gamelan dance accompaniment has one form which includes two sentences, and five motifs. Based on the results of this study it is hoped that it can reactivate the traditional artists in the Ketapang Regency, West Kalimantan. Keywords: Accompaniment Music Analysis, Bajadi Traditional, Gamelan dance